Prevalence of anemia in dialysis patients - Imtiaz Baig; Waqar Ahmad; Mateen Akram; Ibad ur Rahman (Pakistan Journal of Kidney Diseases, 2021)
Anemia is a very common complication in patients with end stage renal disease(ESRD).Clinical trials indicate that improving anemia improves cognitive and sexual function, general well-being, and exercise capacity and reduces the need for blood transfusions. We suspect that in our population on maintenance hemodialysis anemia remains undertreated. Materials and Methods: It was a cross sectional study to determine the prevalence of anemia in patients on maintenance hemodialysis in Department of Nephrology Shaikh Zayed Hospital Lahore. Both male and female from aged 17 years to 70 years whether or notreceiving EPO were included in this study. Patients with acute kidney injury or kidney transplant dysfunction leading to dialysis were excluded. Anemia was defined as Hb< 13.5gm/dl in men and Hb<12gm/dl in women. RESULTS Out of 128 patients, 61 (47.65%) were male and 67 (42.35%) were female. The mean age of the patients was 46.61 years (male: 44.85; female: 48.37). 56 out of 61 males(91.8%) and 61 out of 67 females(91%) had anemia. Mean Hb was found to be 10.59 and 10.07gm/dl in males and females respectively. CONCLUSIONS We concluded that the prevalence of anemia in both male and female ESRD patients on hemodialysis is very high and was present in more than 90% of the patients.